The emerging and diverse roles of F-box proteins in spermatogenesis and male infertility - Zhuang, Xuan; Ruan, Jun; Zhou, Canquan; Li, Zhiming (Cell regeneration, 2024)
F-box proteins play essential roles in various cellular processes of spermatogenesis by means of ubiquitylation and subsequent target protein degradation. They are the substrate-recognition subunits of SKP1–cullin 1–F-box protein (SCF) E3 ligase complexes. Dysregulation of F‑box protein‑mediated proteolysis could lead to male infertility in humans and mice. The emerging studies revealed the physiological function, pathological evidence, and biochemical substrates of F-box proteins in the development of male germ cells, which urging us to review the current understanding of how F‑box proteins contribute to spermatogenesis. More functional and mechanistic study will be helpful to define the roles of F-box protein in spermatogenesis, which will pave the way for the logical design of F-box protein-targeted diagnosis and therapies for male infertility, as the spermatogenic role of many F-box proteins remains elusive.